GOVERNMENTALITY DALAM PENGELOLAAN PARIWISATA BERKELANJUTAN DI KABUPATEN GIANYAR BALI - Permini, Ni Luh Putu Ening; Junaedy, I Kadek Dede; Wahyuni, Made Dewi; Dinata, Ni Luh Komang Cantika Rahayu; Putri, Desak Putu Niken Isma (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
Sustainable tourism management has become a crucial issue in Bali, one of the most popular tourist destinations in Indonesia. The rapid growth of tourism has had negative impacts on the environment and local culture. Therefore, the implementation of governance based on environmental ethics and social inclusion is an important strategy in managing sustainable tourism while preserving Balinese cultural identity. This study examines the implementation of governmentality in sustainable tourism management in Bali. Through community participation and public consultation, the Balinese government integrates input from local communities, academics, and tourism industry stakeholders in tourism decision-making. Environmental ethics is the main focus in tourism management, with strict regulations to protect natural resources and the environment. The results of the implementation of governmentality show positive impacts. Balinese tourism becomes more sustainable with strict environmental monitoring and enforcement of regulations. This increases local community involvement in the tourism industry, ensuring that tourism benefits are distributed to all levels of society. Cultural preservation is also a major concern in tourism policy through the involvement of local communities in decision-making. This study makes a significant contribution to understanding the implementation of governmentality in sustainable tourism management in Bali. It is intended for the government and tourism stakeholders to achieve the right balance between sustainable tourism growth, cultural preservation, and environmental protection in the future.